Implementation of STEAM-based learning to increase motivation to learn mathematics in Grade IV SDN 13 Langsa - Rafli, Muhammad Febri; Siregar, Saswina Hidayah; Riyani, Mufti (Cendikia : Media Jurnal Ilmiah Pendidikan, 2024)
This research emerged on the basis of problems in learning mathematics has not emphasized the indicators of student learning motivation. The effort to overcome these problems with innovative learning is STEAM-based learning. This study aims to analyze the application of Science, Technology, Engineering, Art and Mathematic (STEAM) based learning to increase motivation to learn mathematics on the material of the nets of blocks and cubes in class IV SDN 13 Langsa. The method in this study used Classroom Action Research (PTK) involving 28 students. The research method steps starting from the planning, implementation, observation and reflection stages. Data collection methods include questionnaires of students' math learning motivation, observation and documentation. Qualitative and quantitative data analysis was used to measure the success of math learning motivation and the quality of the learning process. The results showed that math learning motivation increased after the application of STEAM-based learning. In the pre-cycle, the value of math learning motivation obtained an average of 2.64 with student learning success of 18%. In cycle I, the value of math learning motivation obtained an average of 3.14 with student learning success of 68%. In cycle II, the value of mathematics learning motivation obtained an average of 3.84 with student learning success of 100%. Recommendations are the need to strengthen teacher creativity, develop learning innovations and improve student abilities to improve the overall quality of learning.